Mobile Stroke Unit Operational Metrics: Institutional Experience, Systematic Review and Meta-Analysis - Ellens, Nathaniel R.; Schartz, Derrek; Rahmani, Redi; Akkipeddi, Sajal Medha K.; Kelly, Adam G.; Benesch, Curtis G.; Parker, Stephanie A.; Burgett, Jason L.; Proper, Diana; Pilcher, Webster H.; Mattingly, Thomas K.; Grotta, James C.; et al. (Frontiers in Neurology, 2022)
Background The available literature on mobile stroke units (MSU) has focused on clinical outcomes, rather than operational performance. Our objective was to establish normalized metrics and to conduct a meta-analysis of the current literature on MSU performance. Methods Our MSU in upstate New York serves 741,000 people. We present prospectively collected, retrospectively analyzed data from the inception of our MSU in October of 2018, through March of 2021. Rates of transportation/dispatch and MSU utilization were reported. We also performed a meta-analysis using MEDLINE, SCOPUS, and Cochrane Library databases, calculating rates of tPA/dispatch, tPA-per-24-operational-hours (“per day”), mechanical thrombectomy (MT)/dispatch and MT/day. Results Our MSU was dispatched 1,719 times in 606 days (8.5 dispatches/24-operational-hours) and transported 324 patients (18.8%) to the hospital. Intravenous tPA was administered in 64 patients (3.7% of dispatches) and the rate of tPA/day was 0.317 (95% CI 0.150–0.567). MT was performed in 24 patients (1.4% of dispatches) for a MT/day rate of 0.119 (95% CI 0.074–0.163). The MSU was in use for 38,742 minutes out of 290,760 total available minutes (13.3% utilization rate). Our meta-analysis included 14 articles. Eight studies were included in the analysis of tPA/dispatch (342/5,862) for a rate of 7.2% (95% CI 4.8–9.5%, I2 = 92%) and 11 were included in the analysis of tPA/day (1,858/4,961) for a rate of 0.358 (95% CI 0.215–0.502, I2 = 99%). Seven studies were included for MT/dispatch (102/5,335) for a rate of 2.0% (95% CI 1.2–2.8%, I2 = 67%) and MT/day (103/1,249) for a rate of 0.092 (95% CI 0.046–0.138, I2 = 91%). Conclusions In this single institution retrospective study and meta-analysis, we outline the following operational metrics: tPA/dispatch, tPA/day, MT/dispatch, MT/day, and utilization rate. These metrics are useful for internal and external comparison for institutions with or considering developing mobile stroke programs.